Satisfaction with the quality of nursing care among older adults during acute hospitalization in Ghana - Abdul‐Ganiyu Fuseini; Rahinatu Bayi; Afizu Alhassan; Joseph Aniba Atomlana (Wiley, 2022)
Abstract Aim This study assessed the level of satisfaction with the quality of nursing care among hospitalized older adults and the factors associated with it. Design This was a quantitative descriptive cross‐sectional survey. Methods We used a validated questionnaire to collect data from a convenience sample of 206 older adults from three government hospitals in Tamale, Ghana. Data were analysed using descriptive statistics, independent sample t test and one‐way ANOVA. Results Most of the participants (72.3%) reported moderate levels of satisfaction with the quality of nursing care, while 23.8% reported high levels of satisfaction. The association between gender, religion and level of satisfaction with nursing care was not statistically significant. However, patients differed on levels of satisfaction based on healthcare facility: patients at the Tamale Central Hospital were more satisfied with the quality of nursing care than those at the Tamale Teaching Hospital. There is a need for capacity building and sensitization workshops on the rudiments of geriatric care for nurses in the metropolis to serve as an impetus for improvement in the quality of care.